2016
DOI: 10.1002/mop.29644
|View full text |Cite
|
Sign up to set email alerts
|

Acetone evaporation and water vapor detection using a caterpillar‐like microstructured fiber

Abstract: power divider incorporating k/4 transformers is properly designed to feed the array elements. The elements of the array are spaced at a distance of 0.8k 0 from each other in both x-and y-directions.ABSTRACT: A new microstructured optical fiber is presented as a sensor of acetone evaporation. Sensing is performed by observing the time response of the reflected signal at 1550 nm when the device is dipped in acetone or a 50% acetone-50% water mixture. The sensor consists on a caterpillar-like microstructured fibe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…It has also been effectively used to cleave and polish the fiber endfacet [131][132][133][134][135][136][137]. In addition, FIB machining has been employed for fabricating lab-aroundfiber and lab-in-fiber devices such as microgratings [138][139][140][141][142][143][144][145][146][147][148][149][150], microcavities [151][152][153][154][155][156][157][158][159][160], as well as access holes and channels [161][162][163][164][165][166][167][168][169]. It is worth mentioning that the beam shaping structures fabricated on the fiber tip predominate in FIB applications in optical fibers (figure 7).…”
Section: Lof Technologymentioning
confidence: 99%
See 2 more Smart Citations
“…It has also been effectively used to cleave and polish the fiber endfacet [131][132][133][134][135][136][137]. In addition, FIB machining has been employed for fabricating lab-aroundfiber and lab-in-fiber devices such as microgratings [138][139][140][141][142][143][144][145][146][147][148][149][150], microcavities [151][152][153][154][155][156][157][158][159][160], as well as access holes and channels [161][162][163][164][165][166][167][168][169]. It is worth mentioning that the beam shaping structures fabricated on the fiber tip predominate in FIB applications in optical fibers (figure 7).…”
Section: Lof Technologymentioning
confidence: 99%
“…Alternatively, the sample can be inserted through an access channel created in the fiber cladding, leaving the fiber endfacets free for optical access. FIB machining, which enables precise control of the depth and shape of an opening, has been effectively used to mill channels for lateral access to the longitudinal fiber air-holes without interfering with the fiber endfacet [161][162][163][164][165][166][167][168][169].…”
Section: Access Holes and Channelsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are also some drawbacks such the influence of ambient pressure: to overcome it, designs are under study and they are currently in a development stage [ 52 ]. Other fabrication approaches include the cladding functionalization to attach sensing coatings more easily [ 53 ], while ion beam technique is also used to create microfluid channels on the fibre [ 54 ].…”
Section: Nano and Microstructured Materials For Sensingmentioning
confidence: 99%
“…A different approach was followed by Preter et al, where the evaporation of a droplet located at the fiber tip [ 20 ] or in an in-fiber micro-cell [ 21 ] was monitored by means of optical power variations. Tip sensors based on microstructured optical fibers have also been employed to monitor the evaporation of fluids [ 22 , 23 ]. Many other sensing devices have been proposed to detect and monitor VOCs, and thorough reviews can be found in [ 11 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%